Endurance: A Year in Space, A Lifetime of Discovery - Scott Kelly (Doubleday / Penguin Random House, 2017)
The veteran of four space flights and the American record holder for consecutive days spent in space, Scott Kelly has experienced things very few have. Now, he takes us inside a sphere utterly inimical to human life. He describes navigating the extreme challenge of long-term spaceflight, both existential and banal: the devastating effects on the body; the isolation from everyone he loves and the comforts of Earth; the pressures of constant close cohabitation; the catastrophic risks of depressurization or colliding with space junk, and the still more haunting threat of being unable to help should tragedy strike at home -- an agonizing situation Kelly faced when, on another mission, his twin brother's wife, Gabrielle Giffords, was shot while he still had two months in space. Kelly's humanity, compassion, humor, and passion resonate throughout, as he recalls his rough-and-tumble New Jersey childhood and the youthful inspiration that sparked his astounding career, and as he makes clear his belief that Mars will be the next, ultimately challenging step in American spaceflight. Here we see the triumph of the human imagination, the strength of the human will, and the boundless wonder of the galaxy.